2014
DOI: 10.1016/j.ijid.2013.11.015
|View full text |Cite|
|
Sign up to set email alerts
|

High load hepatitis B virus replication inhibits hepatocellular carcinoma cell metastasis through regulation of epithelial–mesenchymal transition

Abstract: siRNAs were able to effectively inhibit HBV replication in vitro. A high load of HBV replication may inhibit the invasion and metastatic ability of HCC cells by reversing the EMT process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A study of the HepG2 and HUH-7 cell lines also suggested that HBx directly upregulates expression of the bHLH transcription factor E12/E47, inhibits E-cadherin expression, and induces the process of EMT [ 115 , 116 ]. In contrast, Wang et al [ 117 ] demonstrated that EMT was suppressed in the HepG2.2.15 cell line in the presence of high levels of HBV virus replication. However, the underlying mechanism is still unclear, and moreover, the effect of virus on EMT in liver cancer may not be dependent only on HBx levels, an issue which requires further investigation.…”
Section: Introductionmentioning
confidence: 96%
“…A study of the HepG2 and HUH-7 cell lines also suggested that HBx directly upregulates expression of the bHLH transcription factor E12/E47, inhibits E-cadherin expression, and induces the process of EMT [ 115 , 116 ]. In contrast, Wang et al [ 117 ] demonstrated that EMT was suppressed in the HepG2.2.15 cell line in the presence of high levels of HBV virus replication. However, the underlying mechanism is still unclear, and moreover, the effect of virus on EMT in liver cancer may not be dependent only on HBx levels, an issue which requires further investigation.…”
Section: Introductionmentioning
confidence: 96%
“…However, contrary to these reports, we have shown that the expression of E-cadherin was upregulated in cells that transiently or stably expressed HBV (Fig 1). Additionally, Wang et al also reported that E-cadherin expression was downregulated following inhibition of HBV replication via silenced by siRNAs in HepG2.2.15 cells [19]. Similar contradictory results have been reported in HCV infection cell models [20].…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, the expression levels of vimentin are also increased in poorly differentiated HCC tissue samples (26,27). Whilst a high load of HBV replication inhibits the EMT of HCC cells (28), HBx is considered to contribute to the promotion of EMT. HBx may be able to induce an EMT phenotype in hepatoma cells, with decreased E-cadherin expression levels as well as an upregulation of vimentin and N-cadherin (29).…”
Section: The Proteins Associated With the Cytoskeleton That Are Deregmentioning
confidence: 99%